Evaluation of the "assessment for continuous treatment with hepatic arterial infusion chemotherapy" scoring system in patients with advanced hepatocellular carcinoma. Issue 3 (7th August 2017) - Saeki, Issei; Yamasaki, Takahiro; Maeda, Masaki; Hisanaga, Takuro; Iwamoto, Takuya; Matsumoto, Toshihiko; Hidaka, Isao; Ishikawa, Tsuyoshi; Takami, Taro; Sakaida, Isao
Abstract : Aim: Sorafenib is the recommended standard of care for advanced hepatocellular carcinoma (HCC) patients. However, hepatic arterial infusion chemotherapy (HAIC) is a treatment option in Asia. We recently developed the assessment for continuous treatment with HAIC (ACTH) score to guide decision‐making for continuous HAIC treatment. The purpose of this study was to validate the utility of the ACTH score in a dedicated cohort. Methods: One hundred and thirty‐one patients with advanced HCC were enrolled in this study (90 in the training group and 41 in the validation group). The point score (range, 0–3) was calculated as follows: Child–Pugh score before HAIC (A = 0, B = 1), α‐fetoprotein (AFP) response (yes = 0, no = 1), and des‐γ‐carboxy prothrombin (DCP) response (yes = 0, no = 1). The AFP and DCP responses were assessed 2 weeks after HAIC induction; a positive response was defined as a reduction of ≥20% from the baseline. Results: The DCP response in the validation group was significantly associated with treatment response, and the median survival time (MST) was longer in patients with an ACTH score ≤1 (15.9 months) than in those with a score ≥2 (7.0 months; P  = 0.002). Survival in all patients showed significant stratification according to the ACTH score; the MSTs associated with scores of 0, 1, 2, and 3 points were 21.7, 14.4, 9.5, and 3.8 months, respectively. Conclusion: The ACTH score can aid in the therapeutic assessment and continued treatment planning of HCC patients receiving HAIC.